Abrasive wear behaviour of conventional and large-particle tungsten carbide-based cermet coatings as a function of abrasive size and type - Kamdi, Z.; Shipway, P.H.; Voisey, K.T.; Sturgeon, A.J. (Elsevier, 2011)
Abrasive wear behaviour of materials can be assessed using a wide variety of testing methods, and the relative performance of materials will tend to depend upon the testing procedure employed. In this work, two cermet type coatings have been examined, namely (i) a conventional tungsten carbide-cobalt thermally sprayed coating with a carbide size of between ∼0.3 – 5 μm and (ii) a tungsten carbide-nickel alloy weld overlay with large spherical carbides of the order of ∼50 – 140 μm in diameter (DuraStell). The wear behaviour of these two materials has been examined by the use of two abrasion tests, namely the micro-scale abrasion test using both silica and alumina abrasives (typically 2-10 μm in size), and the dry sand-rubber wheel test (ASTM G65), again with both silica and alumina abrasives (typically 180 – 300 μm in size). It was found that when the abrasive particles were of the same scale or larger than the mean free path between the hard phase particles, then the matrix phase was well protected by the hard phases. Testing (in both test types) with alumina abrasives resulted in wear of both the hard carbide phases and the matrix phases in both the thermally sprayed coating and the weld overlay, with the thermally sprayed coating exhibiting lower wear rates. The wear behaviour of the materials with the more industrially relevant silica abrasive was more complex; the thermally sprayed coating exhibited a lower wear rate than the weld overlay with the fine abrasive in the micro-scale abrasion test due to effective shielding of the matrix from abrasive action due to the fine reinforcement particle size. In contrast, with the coarser silica abrasive in the dry sand-rubber wheel test, the weld overlay with the large carbides was able to provide matrix protection with low rates of wear, whereas the thermally sprayed coating wore by fracture of the more brittle microstructure. These findings demonstrate the importance of selection of appropriate laboratory test procedures and abrasives to simulate behaviour of materials in service environments.